Intestinal structural changes in malnutrition and moderate injury - Valiñas, Roberto; Méndez, Estela; Castro, Martha; Cura, Leandro; Chifflet, Carla; Borgno, Laura; Bertullo, Hugo (Cirugía del Uruguay, 1994)
The authors carry out a prospective study in which the effect of two variables is analysed: simple malnutrition and modera te injury, represented by the collocation of a central venous via, over intestinal morphology in a group of tars. Results were analysed by means of a « T» test, paying special attention to the height of the intestinal villi, depth of the crypt and number of mitosis. As related to animal weight; no significant changes were observed either in the control group or in those submitted to injury and malnutrition.